(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Augmented applications are a digital marketing strategy businesses use to allow customers to view their chosen product using their mobile phones in real time. Businesses face challenges in terms of customer acceptance as augmented applications emerge. This research aimed to determine the use of the augmented application (IKEA app) in IKEA Company’s digital marketing in terms of its process, its usefulness in digital marketing, and its advantages and disadvantages. This study used the descriptive research method of design, with 30 users of an augmented application as respondents, and it used the purposive sample technique. Documentary analysis and questionnaires were used to answer the research questions, and statistical tools such as frequency and percentage, weighted mean, and ranking were used. The following conclusions were drawn from the preceding analysis and interpretations of results: the process of using the augmented application in terms of room/pace scanning, selecting furniture, and purchasing was easy to use and navigate; the utilization of augmented application response as "Strongly Agree" in terms of room/place scanning, selection of furniture and purchasing, augmented application as a helpful tool in digital marketing response as to "Extremely Helpful," The advantages was it increased product information and the disadvantage was it lacks privacy and security of users data there is a proposed marketing strategies to improve the utilization of augmented application. Based on the findings, the following recommendations are made: continue to have relevant products in today’s time, train each employee on how to fix bug issues in the application, and add more interesting features to increase customers’ experience. The company will use the data to improve its augmented application as a digital marketing tool to maintain good customer relationships.